New insights into the genetic structure of the outbreak-prone bamboo grasshoppers - Song, Zimeng; Ze, Sangzi; Liu, Chunxiang; Chen, Bing (Frontiers in Ecology and Evolution, 2023)
The genetic structure of species is shaped by natural (e.g. terrain, climate) and non-natural (e.g. human activities) factors. Geographical isolation and natural barriers are important causes of genetic structure formation of species. Here, we explored this issue in bamboo grasshoppers, Ceracris kiangsu, which is an important pest that feeds on bamboo in East and Southeastern Asia. Based on 186 newly sequenced and 286 previously sequenced mitochondrial COI fragments, and 8 nuclear microsatellite loci, we examined the genetic diversity and population genetic structure of C. kiangsu. The degree of genetic differentiation among populations was also high, and Mantel test showed that it was significantly correlated with geographical distance. Principal coordinate analysis and STRUCTURE results revealed two genetically different groups, a South China (S-China) Group and a Southeast Asia (SE-Asia) Group. Climate variables partly explained the population genetic structure. The demographic history and ABC showed that the S-China Group experienced population expansion, whereas the SE-Asia Group was consistently stable. Our study demonstrates an obvious population structure maintained in this migratory insect and reveals the potential effect of past climatic change, geographical isolation, and ecological factors on the evolution of their genetic structure.